Study of defecation disorders in elderly patients - Corrêa Neto,Isaac José Felippe (2020)
Abstract Introduction: Defecation disorders, whether anal incontinence or chronic intestinal constipation, are frequent pelvic floor alterations in the general population and are more common in those with risk factors,i.e., in the elderly, women with an obstetric background, and those with comorbidities, history of pelvic radiotherapy, diabetics, the bedridden, or those with history of orifice surgery, among others. Objective: To analyze the incidence of defecation disorders in geriatric patients treated at the Medical Specialties Outpatient Service (MSOS) of Hospital Santa Marcelina. Methods: Prospective, randomized study that interviewed the same patients in two moments: 1) subjective anamnesis through spontaneous history and 2) objective anamnesis with specific questionnaires to assess anal incontinence and chronic constipation. Results: Between March 2016 and June 2017, 149 patients were analyzed, of whom 114 (76.5%) were female, with a similar mean age between genders; 51.67% had symptoms of anal incontinence and/or chronic constipation. Only 35.5% of patients with complaints of fecal leakage or flatus spontaneously reported them, while 87.1% of constipated patients did so. In the present study, no significant correlation was observed between the mode of delivery (p = 0.106), pregnancy (p = 0.099), and the number of deliveries (p = 0.126) with anal incontinence. In turn, there was no higher incidence of chronic intestinal constipation in females (p = 0.099) and most patients with this complaint had Bristol type 1 or 2 stools. Conclusion: The incidence of defecation disorders in the geriatric population is high and, most notably, anal incontinence is not spontaneously reported by most patients.